UNAIDS Action Framework : Universal Access for Men who have Sex with Men and Transgender People. - UNAIDS (Unaids Publication, 2009)
Business as usual is no longer a viable response to the HIV-related risks of men who have sex with men and transgender people. Where data exist on HIV in these populations, they show that our collective responses are failing far more often than they are reaching scale or succeeding. Just as disconcerting, in many parts of the world, is the fact that few reliable data exist at all.